Offence characteristics: a comparison of lone, duo, and 3+ perpetrator robbery offences. Issue 2 (7th February 2021) - Wüllenweber, Sarah; Burrell, Amy
ABSTRACT: The current study investigated characteristics of robbery offences with a focus on lone versus multiple perpetrator crimes. The main aim was to outline differences between lone, duo, and 3+ perpetrator crimes. Police recorded crime data from West Midlands Police relating to 1574 personal robberies (including attempts) committed in Birmingham city centre (UK) were used in the analysis. Robbery offences were compared on victim and offender demographics and offence characteristics. The findings showed significant differences between the three group sizes (lone, duo, 3+ offenders) in victim and offender age; approach styles; victim control variables; weapon use; alcohol and violence; injuries; and carjacking. The findings of the current research can feed into developing policing strategies which take into account differences in group size.